Electrocardiograph (ECG) circuit design and software-based processing using LabVIEW - Abdul Jamil, M.M.; Soon, C.F.; Achilleos, A.; Youseffi, M.; Javid, F. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
The efficiency and acquisition of a clean (diagnosable) ECG signal dependent upon the proper selection of electronic components and the techniques used for noise elimination. Given that the human body and the lead cables act as antennas, hence picking up noises from the surroundings, thus a major part in the design of an ECG device is to apply various techniques for noise reduction at the early stage of the transmission and processing of the signal. This paper, therefore, covers the design and development of a Single Chanel 3-Lead Electrocardiograph and a Software-based processing environment. Main design characteristics include reduction of common mode voltages, good protection for the patient, use of the ECG device for both monitoring and automatic extraction (measurements) of the ECG components by the software. The hardware consisted of a lead selection stage for the user to select the bipolar lead for recording, a pre-amplification stage for amplifying the differential potentials while rejecting common mode voltages, an electrical isolation stage from three filtering stages with different bandwidths for noise attenuation, a power line interference reduction stage and a final amplification stage. A program in LabVIEW was developed to further improve the quality of the ECG signal, extract all its features and automatically calculate the main ECG output waveforms. The program had two main sections: The filtering section for removing power line interference, wideband noises and baseline wandering, and the analysis section for automatically extracting and measuring all the features of the ECG in real time. A Front Panel Environment was, therefore, developed for the user interface. The present system produced ECG tracings without the influence of noise/artefacts and provided accurate detection and measurement of all the components of the ECG signal.